Small and medium-sized business in Malaysian economy: case of Turkish entrepreneurs in Kuala Lumpur - Kayadibi, Saim; Polat, Refik; Fidan, Yahya (World Business Institute, 2013)
Small and medium-sized businesses (SMSB) become increasingly important for the whole world with their compatibility and flexibility structures. These small and Medium-sized business, which provide a large portion of production with their adaptability features in changes, which play a significant role in economies in the rapidly changing and intense competition world as well. In this study, it is aimed to investigate the common problems of Turkish origin SMSB operating in the capital city Kuala Lumpur of Malaysia will be examined in terms of governance and efficiency. The subject matter will be investigated theoretically on the basis of business through conducting survey and questionnaire methods which will be analyzed by SPSS. Keywords: Turkish Investors; Entrepreneurship; Management; Organization; Malaysian Economy. JEL Codes: A11, L26, F21 and O53